United Nations Disarmament Yearbook 1981 - United Nations Office for Disarmament Affairs (United Nations, 1981)
The volume 6 compiles the disarmament resolutions and decisions of the General Assembly, the voting patterns in the General Assembly and the First Committee report and dates of their adoption.